Inulin Reverses Intestinal Mrp2 Downregulation in a Diet-Induced Obesity Mouse Model: Role of Intestinal Microbiota as a Pivotal Modulator - Zecchinati, Felipe (2025)
Background: The intestinal microbiota (IM) modulates host physiology, and its alteration (dysbiosis) is associated with numerous diseases, including obesity. This condition influences the pharmacokinetics of drugs prescribed for related comorbidities, although the underlying mechanisms remain poorly understood. Mrp2, an essential ABC transporter of the intestinal biochemical barrier, regulates the absorption of dietary toxins and orally administered drugs, modulating their bioavailability. However, its regulation in the obesity context is poorly characterized, and the role of IM alteration in this process remains unknown. Objective: To evaluate the role of the IM as a key factor, along with downstream candidate mediators, in the regulation of Mrp2 under obesity conditions. Methods: Male C57BL/6 mice were fed either a control diet or High-Fat Diet (HFD) for 8 weeks, followed by 2 weeks with or without 5% inulin, a well-known prebiotic, supplementation. Metabolic and biochemical parameters were evaluated. Intestinal barrier integrity, inflammatory cytokines, oxidative stress (OS) markers, and plasma endotoxin levels were assessed. Mrp2 expression was analyzed at mRNA and protein levels, and transporter activity was determined using the everted intestinal sac model. Fecal microbiota composition was characterized by 16S rRNA sequencing. Results: HFD feeding induced obesity, insulin resistance, hyperglycemia, dyslipidemia, intestinal dysbiosis, elevated endotoxemia, barrier dysfunction, inflammation, and OS. These alterations were associated with a marked downregulation of Mrp2 expression and activity. Inulin supplementation restored IM composition, improved metabolic and intestinal parameters, and reduced inflammation and OS. These positive changes correlated with normalization of Mrp2. Conclusions: Our findings provide the first evidence that intestinal dysbiosis, inflammation, and OS act as a central regulatory axis of intestinal Mrp2 in obesity, with the IM functioning as a key modulator.